Baryogenesis in the vMSM: recent developments* - Timiryasov Inar (EPJ Web of Conferences, 2018)
Extension of the Standard Model with two right-handed neutrinos provides an economic and testable explanation of the origin of the baryon asymmetry of the Universe. We review recent progress in understanding dynamics of the asymmetry generation. We also present results of a new study of the parameter space of the model. These results demonstrate that the region of the parameter space in which the observed value of baryon asymmetry can be reproduced is larger than it was previously obtained.